Analysis of serum immunoglobulin level in children with Burkitt lymphoma - Zhang, M (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To summarize changes of serum immunoglobulin levels before and after chemotherapy in children with Burkitt lymphoma (BL), so as to investigate the effects of chemotherapy and rituximab on serum immunoglobulin levels in children with BL. Methods: Clinical data of 223 children with newly diagnosed Burkitt lymphoma at Beijing Children's Hospital from January 2009 to April 2017 were analyzed retrospectively. They were treated according to the modified LMB 89 regimen and some of them received combined rituximab therapy during the chemotherapy. The serum immunoglobulin (IgA, IgM, IgG) before chemotherapy, at the time of discontinuing chemotherapy, as well as 6, 12, 24, 36 months after chemotherapy were collected. Changes of serum IgA, IgM and IgG with time among different treatment groups were compared using repeated measures ANOVA. Results: According to risk group, 223 children were devided into group B（n=53）and group C（n=170）. Before chemotherapy, 109 cases (48.9%) were combined with hypogammaglobulinemia. The serum IgA, IgM, and IgG levels of all the patients were (0.9±0.7), 1.2 (0.5, 1.3) and (7.2±2.9) g/L before chemotherapy, (0.5±0.4), 0.2 (0.1, 0.3) and (6.3±2.3) g/L at the time of discontinuing chemotherapy (t=13.63, Z=-11.99, t=4.57, all P<0.05). There were statistical difference in IgA, IgM levels of group B and IgA, IgM, IgG levels of group C before chemotherapy and at the time of discontinuing chemotherapy (t=8.86, Z=-6.28, t=11.19, Z=-10.15, t=4.50, all P<0.05). The differences of serum IgA and IgG levels at the time after chemotherapy among patients treated with chemotherapy alone and those treated with chemotherapy combined rituximab in group B and C were significant (F=5.38, P=0.002 and F=4.22, P=0.007). Conclusions: Approximately half of children with BL have already existed hypogammaglobulinemia at initial diagnosis prior to the start of treatment. The modified LMB 89 regimen have significant effect on humoral immunity of children with BL. In the process of immune reconstruction after chemotherapy, rituximab has more significant effect on serum IgA and IgG levels in BL patients